Le tourisme, entre ordinaires et extraordinaires de la géographie scolaire - Sophie Gaujal; Caroline Leininger-Frézal (Bulletin de l’Association de Géographes Français)
Ordinary practices at school present an enchanted vision of tourist areas, often reduced to seaside tourism practiced in a few small islands around the world and organized around luxurious facilities. This vision, however, can be complicated by accompanying this geography of tourism from a geography through tourism. The postcard image then gives way to the implementation of a geographical reasoning, mobilizing actors, scales and spatial dynamics.